Applying Eggshell Powder to Improve the Soil Quality of Durian Orchard Gardens in Dong Thap Province - Nhat Ha, Le; Thu, Tran Thi Tuyet; Tan Dung, Nguyen (VNU Journal of Science: Earth and Environmental Sciences; Vol 42 No 2, 2026)
Durian is one of the most delicious tropical fruit plants with critical commercial value, but it is challenging to grow under degraded soil conditions. This study aimed to determine selected physicochemical properties of durian-growing soils at three orchard sites in Dong Thap province and measure the effectiveness of eggshell powder (EP) in improving soil quality at added rates of 0%, 0.5%, 1%, 1.5%, and 2%. Pre-batched soil analysis showed the following values: pH KCl ​: 3.51-3.76; pH H2O ​: 4.45-4.85, EC: 0.107-0.219 dS m -1 ; OM: 2.04-3.14%, Ca²⁺: 0.07-0.13 meq 100g -1 ; Mg²⁺: 0.32-0.52 meq 100g -1 , and high levels of available and total N, P, K. After incubating the soil with eggshell powder at rates of 0-2% for 14 days, the results of analyses revealed that pH H2O increased sharply to 6.47-7.25 and pH KCl reached 6.40-7.15; Ca²⁺ reached 0.70-0.90 meq 100g -1 , OM rose to 2.73-3.48%. Total and available concentrations of N, P, and K did not show significant changes. The eggshell powder amendment markedly improved soil acidity and exchangeable Ca²⁺ content. At added rates of 0-2%, soil salinity remained below the harmful threshold (EC < 0.30 dS m -1 ). This study proposes using eggshell powder to improve soil acidity for durian cultivation.